2016
DOI: 10.1002/jmri.25331
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DWI implemented after DCE-MRI yields increased specificity for BI-RADS 3 and 4 breast lesions

Abstract: Quantitative DWI has a lower NPV compared to DCE-MRI for evaluation of breast lesions and may therefore not be able to replace DCE-MRI; when implemented after DCE-MRI as problem solver for BI-RADS 3 and 4 lesions, the combined specificity improves significantly. J. Magn. Reson. Imaging 2016;44:1642-1649.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…Diffusion‐weighted imaging (DWI), a common functional MRI technology, is widely used to describe the diffusion of water in living tissue by the apparent diffusion coefficient (ADC) . The ADC quantifies the monoexponential decay of signal intensity (SI), which reflects information related to the tumor microenvironment, such as cellularity, extracellular space, and the integrity of the cell membranes in a noninvasive manner . At present, DWI has been reported to be a strong adjunct to standard clinical MRI protocols …”
mentioning
confidence: 99%
“…Diffusion‐weighted imaging (DWI), a common functional MRI technology, is widely used to describe the diffusion of water in living tissue by the apparent diffusion coefficient (ADC) . The ADC quantifies the monoexponential decay of signal intensity (SI), which reflects information related to the tumor microenvironment, such as cellularity, extracellular space, and the integrity of the cell membranes in a noninvasive manner . At present, DWI has been reported to be a strong adjunct to standard clinical MRI protocols …”
mentioning
confidence: 99%
“…IVIM-DWI technology has been applied in the diagnosis of many diseases, e.g. carcinomas, lesions or infections, but so far its application in hypothalamic feeding studies was only rarely reported [30,31,32]. This might be due to the tiny volume of hypothalamus the low magnetic field of which might be easily distorted.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, other functional MRI parameters such as DWI have been implemented in clinical routine, as several studies have demonstrated that DWI with ADC mapping improves diagnostic accuracy in breast cancer . In addition, DWI with ADC mapping has been assessed for correlations of ADC values and molecular breast cancer subtypes .…”
Section: Breastmentioning
confidence: 99%
“…109 Recently, other functional MRI parameters such as DWI have been implemented in clinical routine, as several studies have demonstrated that DWI with ADC mapping improves diagnostic accuracy in breast cancer. [111][112][113][114][115] In addition, DWI with ADC mapping has been assessed for correlations of ADC values and molecular breast cancer subtypes. [116][117][118] All studies independently discovered that HER2-positive cancers had the highest ADC values, whereas luminal B cancers without HER2 overexpression had the lowest ADC values.…”
Section: Molecular Breast Cancer Subtypesmentioning
confidence: 99%